The Effect of Podcast on the Achievement of the Students — a Case Study In Malaysia - Wong, Ling Shing; Chan, Chang Tik; Mohamad Hanefar, Shamsiah Banu (INTI International University, 2011)
Podcast Is a tool 1o- blended learning which media files are made available online as a reference material for students. As podcast received many positive responses [rom many foreign educators, a local study was conducted to probe the responses of the local students to podcast. The study was done by a survey on students’ perspective over the usage of podcast, as well as a measurement on the effectiveness of podcast through the achievement of the students. The students were divided into two major groups- blended Learning with podcast and blended Learning without podcast. From the study, majority of the students gave positive feedback over the usage of the blended learning approaches, as well as podcast. In addition to that, through statistical analysis, the overall achievement of the students with podcast was significantly better than the students without podcast. As conclusion, podcast can be a good tool to convey more effective teaching and learning process in Malaysia. However, a study with wider coverage and more subjects should be conducted to get a better picture about the usage of podcast In Malaysia.